Strategi dan Media Pembelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah - Atik Fauziah; Lailatul Maqhfiroh; Alifa Retna Handriyansari (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The subject of Islamic Cultural History is one of the subject that is somewhat less interesting for student feel sleepy. This is heavily influenced by factors in the learning process that are less fun and lack the creativity of a theacher in the teaching and learning process when interacting with student in the classroom. SKI material whose characteristics are past Islamic history material is conveyed or oven told casually with a lecturing or storytelling learning model. This kind of learning model makes students just sit and listen to what is conveyed by the teacher so that creative thinking and student material capture are not optimal. To overcome this problem a theacher must have many strategies in conveying a lessonass well as involving the media in its delivery. Therefore, in this article we will discuss strategies and media that can be used in learning the history of Islamic culture. With the aim of providing insight for teachers and providing insight for teachers in delivering good, effective and innovative learning materials. Keywords: History of Islamic Culture; Strategy; Media.